The impact of age and intensity of treatment on the outcome of traumatic brain injury - Corriero, Alberto; Fornaciari, Anna; Terrazzino, Samuel; Zangari, Rossella; Izzi, Antonio; Peluso, Lorenzo; Savi, Marzia; Faso, Chiara; Cavallini, Laura; Polato, Martina; Vitali, Eva; Schuind, Sophie; et al. (Frontiers in Neurology, 2024)
BackgroundApproximately one-third of trauma-related deaths are due to traumatic brain injury (TBI), particularly among young adults and elderly patients. Management strategies may vary across different age groups, potentially influencing short-term neurological outcomes. This study aims to investigate age-related disparities in treatment approaches and 3-month neurological outcomes among TBI patients.MethodsWe conducted a retrospective study on TBI patients requiring Intensive Care Unit (ICU) admission from January 1, 2015, to January 1, 2024, in a tertiary University hospital. Patient demographics, major comorbidities, ICU admission parameters, interventions and ICU complications were collected. An unfavorable neurological outcome at 3 months (UO) was defined as a Glasgow Outcome Scale (GOS) score of 1–3. A high therapy intensity level (TIL) was defined as a TIL basic of 3–4. A multivariable logistic regression model and a Cox proportional Hazard Regression model were used to assess the association of age and TIL with neurological outcome and mortality. A sensitivity analysis on low TIL (0–2) and high TIL subgroups was also conducted.ResultsWe enrolled 604 TBI patients, of which 240 (40%) had UO. The highest prevalence of UO was found in patients aged ≥80 years (53/94, 56%), followed by patients aged 50–79 years (104/255, 41%). The age group 35–49 years had the lowest rate of UO (38/127, 30%). Older patients (age ≥ 80 years) received less frequently high TIL than others (p = 0.03). In the multivariable analysis, age ≥ 80 years [OR: 3.42 (95% CI 1.72–6.81)] was independently associated with UO, while age ≥ 80 years [HR 5.42 (95% CI 3.00–9.79)] and age 50–79 years [HR 2.03, (95% CI 1.19–3.48)] were independently associated with mortality. Although there was no interaction between age groups and TIL on outcome, an exploratory analysis showed that in the high TIL subgroup of patients, age had no independent impact on the outcome, whereas, in the low TIL group, age ≥ 80 years was independently associated with UO [OR: 3.65 (95% CI: 1.64–8.14)].ConclusionOlder age, especially in the setting of low intensity treatment, may impact short-term neurological outcome of traumatic brain-injured patients.